ПРЕДИКАТЛАР ВА КВАНТОРЛАР ЁРДАМИДА ТЕОРЕМАЛАРНИ ТУЗИШ (Scientific journal of the Fergana State University, 2023)
This article discusses the use of discrete mathematics and mathematical loqic in the relay-contact circuits, the design of automatic circuits and programming.